Nf2 Mutation in Schwann Cells Delays Functional Neural Recovery Following Injury. (15th March 2018) - Truong, Kristy; Ahmad, Iram; Jason Clark, J.; Seline, Alison; Bertroche, Tyler; Mostaert, Brian; Van Daele, Douglas J.; Hansen, Marlan R.
Highlights: Nf2 mutation in Schwann cells (SCs) results in delayed neural recovery as measured by the Cat Walk. Nf2 mutation in SCs results in reduced axon density but does not result in a significant reduction in axon regeneration. Nf2 mutation in SCs results in a significant increase in extracellular matrix deposition. Nf2 mutation in SCs does not result in a significant difference in conduction velocity or amplitude 90 days post-injury. Abstract: Merlin is the protein product of the NF2 tumor suppressor gene. Germline NF2 mutation leads to neurofibromatosis type 2 (NF2), characterized by multiple intracranial and spinal schwannomas. Patients with NF2 also frequently develop peripheral neuropathies. While the role of merlin in SC neoplasia is well established, its role in SC homeostasis is less defined. Here we explore the role of merlin in SC responses to nerve injury and their ability to support axon regeneration. We performed sciatic nerve crush in wild-type (WT) and in P0SchΔ39–121 transgenic mice that express a dominant negative Nf2 isoform in SCs. Recovery of nerve function was assessed by measuring mean contact paw area on a pressure pad 7, 21, 60, and 90 days following nerve injury and by nerve conduction assays at 90 days following injury. After 90 days, the nerves were harvested and axon regeneration was quantified stereologically. Myelin ultrastructure was analyzed by electron microscopy. Functional studies showed delayed nerve regeneration in Nf2 mutant mice compared to the WT mice. Delayed neural recovery correlated with a reduced density of regenerated axons and increased endoneurial space in mutants compared to WT mice. Nevertheless, functional and nerve conduction measures ultimately recovered to similar levels in WT and Nf2 mutant mice, while there was a small (∼17%) reduction in the percent of regenerated axons in the Nf2 mutant mice. The data suggest that merlin function in SCs regulates neural ultrastructure and facilitates neural regeneration, in addition to its role in SC neoplasia.